The Role of Assistive Technologies in Teaching English to Learners with Disabilities in Home-Based Education (The Journal of Interdisciplinary Human Studies, 2026)
This article examines the role of assistive technologies (AT) in facilitating English language instruction for learners with disabilities within home-based educational settings. As inclusive education continues to expand globally, home-based education has emerged as a viable alternative for students whose disabilities make traditional classroom attendance challenging. The integration of assistive technologies, ranging from screen readers and speech-to-text software to augmentative and alternative communication (AAC) devices, has significantly transformed the pedagogical landscape for these learners. Drawing on current literature, this paper explores the types of assistive technologies available, their effectiveness in improving English language skills (reading, writing, listening, and speaking), the challenges encountered by educators and families, and recommendations for optimizing AT-supported home-based English instruction. The findings suggest that when appropriately selected and implemented, assistive technologies can substantially enhance language learning outcomes, foster learner autonomy, and promote meaningful educational inclusion for students with disabilities.
Keywords: assistive technology; English language teaching; disabilities; home-based education; inclusive education; augmentative and alternative communication